Evaluation of the Significance of Production Rates in Reduction of Wax Precipitation and Deposition thickness in a flowline - Bright Bariakpoa Kinate; Joseph Atubokiki Ajienka; Sunday Sunday Ikiensikimama (Penerbitan Universitas Trisakti, 2021)
Investigating wax formation tendencies in flow line for different rates of production will assist in decision making in determining the location of wax formation and point of wax modifiers injection. In this work, experimental and field data of Niger Delta field waxy crude oil samples were modeled and simulated with Multiflash and exported to OLGA software to investigate the wax formation tendencies in flow line. The properties of the waxy crude oil were modeled and characterized in multiflash and exported to OLGA. What if analysis of five case scenarios (Base case (14,000 bbl/day)), Production turndown case (10000 bbl/day and 12000 bbl/day), Production Ramp-up case (16000 bbl/day) and 18000 bbl/day) were run with Rygg, Rydahl, and Ronningsen (RRR) model for 100 days in a 16 inches flow line of 28500 ft length. For crude oil sample 1 with a production rate scenario of 14000 bbl/day (24,176 kg/s), the wax settles at a distance of 15625 ft from the wellhead. For a production rate scenario of 12000 bbl/day, the deposition is 303 ft closer than the base case. For the scenario of a flow rate of 10000 bbl/day, the deposition occurs 2871 ft closer to the base case. For the scenario of a flow rate of 16000 bbl/day the deposition is 4563 ft further from the base case. Meanwhile, for the scenario of a flow rate of 18000 bbl/day, the deposition of 7163 ft is further from the base case condition. Increase in the rate of production for the three crude samples prolong wax precipitation downstream the flow line. In addition, the thickness of wax deposited increases gradually with the production rate and exhibit a comparable relationship with the specific mass of wax. The precipitation rate is not linear with the rate of production and depends on other properties of the crude. Producing waxy crude at a higher rate will minimize wax formation and deposition tendencies in flow line in the field.